The Implications of Albert Bandura's Social Learning Theory in the Creation of Homilies by Indonesian Catechists - Martinus Dendo Ngara; Silvana Natalia Nainggolan (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
This study was motivated by a real problem in the Catholic Church in Indonesia, where homilies delivered by catechists are often considered boring, unstructured, and lacking in spiritual inspiration for the congregation. The main objective of this study is to offer practical solutions through the application of Albert Bandura's Social Learning Theory (SLT), specifically through modeling methods to improve the preaching skills of catechists. The method used was qualitative discourse to explore Bandura's theory and in-depth interviews with active catechists in the regions of Java, Medan, Flores, and Sumba, who were selected using purposive sampling techniques. The results of the study show that catechists effectively use role models from various backgrounds to follow the four stages of modeling: attention, retention, behavior production, and motivation. Important elements studied include depth of content, structured thinking, use of humor, vocal techniques, and mastery of verbal and non-verbal language. By adopting this strategy, catechists are able to overcome the crisis of preaching and deliver a more lively and inspiring message to their listeners. As a suggestion for further research, it is recommended to examine the effectiveness of digital platforms as a source of modeling for young catechists and the impact of formal evaluation systems by the faithful on the professionalism of their preaching in order to ensure the quality of liturgical preaching in the future.